THEORETICAL AND EXPERIMENTAL INVESTIGATIONS OF A WATER HAMMER IN SAVA RIVER KAPLAN TURBINE HYDROPOWER PLANTS - Bergant, Anton; Mazij, Jernej; Pekolj, Jošt (Journal of Energy Technology, 2025)
This paper deals with critical flow regimes that may induce an unacceptable water hammer in the Sava River Kaplan turbine hydropower plants. The rigid water hammer model is introduced first. The computational results are then compared with the results of measurements in two distinct hydropower plants (HPP): (i) The refurbished and upgraded Medvode HPP, and (ii) The newest Brežice HPP. Comparisons of the computed and measured results are examined for normal operating regimes. The water hammer in the two power plants is controlled by appropriate adjustment of the wicket gates and runner blades closing/opening manoeuvres. The agreement between the computed and measured results is reasonable.